CD34 immunoexpression in canine skin follicular tumors and basal cell carcinomas: case series report - Firmo, Bruna Fernanda [UNESP]; Grandi, Fabrizio [UNESP]; Cogliati, Bruno; Rocha, Noeme Sousa [UNESP] (My University, 2014)
Back ground: Basal cell carcinomas and follicular tumors are relatively common skin neoplasms both in veterinary and human medicine. Currently, it is believed that stem cells are important for skin tumor development. Hypothesis/objective: the objective of the study was to characterize CD34 expression in canine follicular tumors and basal cell carcinoma in order to investigate the possible role of these cells in skin tumorigenesis. Animals & Methods: eleven skin tumors including basal cell carcinomas and follicular tumors were submitted to immunohistochemistry using the stem cell marker CD34. Results: CD34 labelling was characterized by a fine, granular and diffuses brown cytoplasmic staining both in control (endothelial cells) and neoplastic cells. Two BCC and one trichoepithelioma displayed positive neoplastic cells and/or fibroblast-like stromal cells. Conclusion: preliminary results described here should be confirmed by large scale studies in order to clarify the potential role of stem cells on human and canine skin tumors.
Keywords: Mammary carcinoma; Diagnosis; Histopathology; Dog